131I therapy in patients with benign thyroid disease does not conclusively lead to a higher risk of subsequent malignancies - Verburg, F. A.; Luster, M.; Lassmann, M.; Reiners, C. (Nuklearmedizin - NuclearMedicine, 2011)
Due to its excellent tolerability and low incidence of side effects, 131I therapy has been the treatment of choice for benign thyroid diseases for over 60 years. A potentially increased risk of malignancies due to this therapy is however still subject of debate. Aim: To review the literature pertaining to 131I therapy of benign thyroid diseases in order to establish whether there is an increased incidence of, or increased mortality due to malignancies of the thyroid or other organs. Methods: In order to allow for sufficient long-term follow-up time after 131I therapy, only literature after 1990 was reviewed. Two criteria were applied to consider an increased incidence of malignancies linked to 131I therapy: a) there should be a latency period of at least 5 years between 131I therapy and the observation of an increased risk b) an elevated risk should increase with increasing radiation exposure. Results: A total of 7 studies reporting cancer incidence and / or mortality in 4 different patient collectives spanning a total of 54 510 patients over an observation period varying from 2-49 years were found. Although some studies detected a slightly increased risk for malignancies of the thyroid or the digestive system, others did not find these effects - while other studies even reported a slightly lower risk of malignant (thyroid) disease after 131I therapy for benign thyroid diseases. Conclusion: As over 60 years of experience has thus far failed to produce conclusive evidence to the contrary, it can be concluded that there is no increased risk of malignancies after 131I therapy for benign thyroid disease.
Keywords: 131I treatment; benign thyroid disease; malignancy; incidence